Unveiling the power of microenvironment in liver regeneration: an in-depth overview - Hu, Yuelei; Wang, Ruilin; An, Ni; Li, Chen; Wang, Qi; Cao, Yannan; Li, Chao; Liu, Juan; Wang, Yunfang (Frontiers in Genetics, 2023)
The liver serves as a vital regulatory hub for various physiological processes, including sugar, protein, and fat metabolism, coagulation regulation, immune system maintenance, hormone inactivation, urea metabolism, and waterelectrolyte acid-base balance control. These functions rely on coordinated communication among different liver cell types, particularly within the liver's fundamental hepatic lobular structure. In the early stages of liver development, diverse liver cells differentiate from stem cells in a carefully orchestrated manner. Despite its susceptibility to damage, the liver possesses a remarkable regenerative capacity, with the hepatic lobule serving as a secure environment for cell division and proliferation during liver regeneration. This regenerative process depends on a complex microenvironment, involving liver resident cells, circulating cells, secreted cytokines, extracellular matrix, and biological forces. While hepatocytes proliferate under varying injury conditions, their sources may vary. It is well-established that hepatocytes with regenerative potential are distributed throughout the hepatic lobules. However, a comprehensive spatiotemporal model of liver regeneration remains elusive, despite recent advancements in genomics, lineage tracing, and microscopic imaging. This review summarizes the spatial distribution of cell gene expression within the regenerative microenvironment and its impact on liver regeneration patterns. It offers valuable insights into understanding the complex process of liver regeneration.